Evaluation of the predictive value of topoisomerase ii a in patients with breast carcinoma - Hajduk, Magdalena; Olszewski, Wojciech P.; Śmietana, Anetta (Polish Journal of Pathology, 2009)
Although the increasing body of knowledge in the field of immunohistochemistry and molecular biology has allowed for better understanding of the biology of breast cancer; nevertheless, a search is still in progress for new factors that would make it possible to preselect patients and employ target therapies. Predictive factors that arouse interest include topoisomerases. The authors evaluated the response to treatment and survival rates depending on expression of topoisomerase II a (TOP2A) and other predictive factors, as well as assessed treatment effectiveness employing therapeutic schemes based on anthracycline depending on TOP2A expression. The investigations demonstrated that the response to treatment and survival of patients with TOP2A expression were similar to the response and survival of those with tumours demonstrating the presence of other recognized predictors. The employed adjuvant therapy according to anthracycline therapeutic protocols was markedly more effective in TOP2A-positive patients as compared to the remaining individuals. Thus, TOP2A constituted a predictive factor. The study demonstrated that in adjuvant therapy employed in infiltrating ductal carcinoma of the breast, not only HER2 but also TOP2A determination in cancer cells was of importance; for this reason, routine determinations by immunohistochemistry should be performed, especially when anthracycline treatment is planned.